Advances in clinical research on liver disease during pregnancy - LIU Miaomiao (Linchuang Gandanbing Zazhi, 2016)
Liver disease during pregnancy is substantially different from common liver diseases, and it is very important to raise the awareness of such disease and improve the diagnostic level. The literature on liver disease during pregnancy published in recent years is reviewed in this article, and the research advances in the pathogenesis, diagnosis, and treatment of liver disease during pregnancy are summarized.